Electricity production and its effects on carbon dioxide emissions in the Kingdom of Saudi Arabia - Alhajji, Zakiah Radhi; Ali, Mohamed Elsayed Hafez (Journal of natural sciences, life and applied sciences, 2021)
Because of increased demand for electrical energy in the Kingdom of Saudi Arabia, which has resulted in an increase in carbon dioxide emissions, the electricity system in the Kingdom of Saudi Arabia is the largest in the Gulf region and the Arab world, with approximately 61.7 gigatons (GW) of peak demand and 89.2 gigatons (GW) of available capacity in 2018 of electricity power. It has grown rapidly over more than 20 years and has almost doubled in size since 2000. Where we observe that the total carbon dioxide emissions in the Kingdom of Saudi Arabia from 1990 to 2020; where shows rapid growth in emissions of carbon dioxide and greenhouse gases, as it was found that CO2 emissions in 1990 amounted to 151 million metric tons compared to 2011 when it reached about 435 million metric tons, and the increase continued until 2020 when it reached about 530 million metric tons. The comprehensive study relied on time series analysis to carefully analyze the electric energy productivity rate from fossil fuels and the significant amount of carbon dioxide emissions typically resulting from promptly burning fossil fuels to naturally produce electric energy. Therefore, the Kingdom of Saudi Arabia, through Vision 2030 and the Paris Agreement on Climate Change, looks to reduce the rate of carbon dioxide emissions in the field of electric power generation by diversifying the fuels used or replacing them with clean and renewable energy such as solar and wind energy.